The language of sisters - Lamb, Cathy (Kensington Books, 2016)
Toni Kozlovsky can't explain how she knows exactly what her sisters are feeling--only that the connection seems to happen out of the blue, just when they need it most. Since Toni, Valerie, and Ellie were little girls growing up in Communist Russia, their parents have insisted it's simply further proof that the Kozlovskys are special and different.